Redescription of Schizotetranychus ugarovi Wainstein (Acari: Tetranychidae) based on new materials from Iran - Dariush Bastani; Mahdieh Asadi (Persian Journal of Acarology)
Schizotetranychus ugarovi Wainstein is redescribed from new materials collected on Alhagi maurorum (Fabaceae) in Iran, representing a new country for this species.